2016
DOI: 10.1001/jamaoncol.2015.3239
|View full text |Cite
|
Sign up to set email alerts
|

Association of Stromal Tumor-Infiltrating Lymphocytes With Recurrence-Free Survival in the N9831 Adjuvant Trial in Patients With Early-Stage HER2-Positive Breast Cancer

Abstract: Importance Tumor-infiltrating lymphocytes at diagnosis are reported to be prognostic in triple-negative breast cancer. Objective Here we evaluate the association of stromal tumor infiltrating lymphocytes (STILs) with recurrence-free survival (RFS) in N9831 HER2-positive patients treated with chemotherapy or chemotherapy plus trastuzumab. Design H&E tumor slides from patients on N9831 Arm A (standard AC→T chemotherapy) and Arm C (concurrent chemotherapy with trastuzumab) were assessed for STILs. STILs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
135
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(151 citation statements)
references
References 26 publications
10
135
4
2
Order By: Relevance
“…To the best of our knowledge, this is the first study to correlate the role of TIL subtypes with clinico-pathological characteristics in BC patients from Sudan. Several studies have highlighted the importance of CD8 + TIL with patients' overall survival and response to treatment in particular in patients with Triple Negative BC and HER2/neu positive BC [11,18,19,35,36]. In our study, the small number of patients in luminal B breast cancer type renders the comparison difficult, nevertheless, CD8 + TILs were significantly higher in HER2/neu positive BC, which is comparable to state of the art studies in MENA countries and worldwide [16,36].…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…To the best of our knowledge, this is the first study to correlate the role of TIL subtypes with clinico-pathological characteristics in BC patients from Sudan. Several studies have highlighted the importance of CD8 + TIL with patients' overall survival and response to treatment in particular in patients with Triple Negative BC and HER2/neu positive BC [11,18,19,35,36]. In our study, the small number of patients in luminal B breast cancer type renders the comparison difficult, nevertheless, CD8 + TILs were significantly higher in HER2/neu positive BC, which is comparable to state of the art studies in MENA countries and worldwide [16,36].…”
Section: Discussionsupporting
confidence: 71%
“…However, recent findings have shown that patients with early stage HER2/neu positive BC and high TILs do not require anti-HER2 therapy [19], this finding may be significant for our group of patients in economically challenged societies where anti-HER2 treatment (such as trustazumab) is neither subsidized nor available [17,18,21].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Breast cancer has a more favorable prognosis among several other major solid tumors such as lung, colon, ovarian, stomach and liver (www.sser.cancer.gov). It is not coincidental that concomitant anti-tumor immunity is also more prominent in breast cancer [29][30][31][32]. Biopsy and surgery tumor samples from breast cancer patients consistently indicated heightened immune responses characterized by presence of large numbers of T cells that coincide with destruction of tumor structure and inhibition of tumor replication (our unpublished observation and [33].…”
Section: Introductionmentioning
confidence: 95%